Functional Endoscopic Sinus Surgery in Management of Pott's Puffy Tumor in a Pregnant Woman: A Clinical Case Report and Literature Review - Seyed Ali Dehghan Manshadi; Azin Tabari; Hana Saffar; Faeze Salahshour; Nahid Shafiee; Azam Sadat Izadpanah; Seyed Mohammad Piri (Clinical Case Reports)
ABSTRACT PPT is a life‐threatening intracranial complication, which is essential to be considered in both children and adults presenting with sinusitis symptoms.